(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
United Nations World Tourism Organization (UNWTO, 1988) has defined sustainable tourismas „‟leading to management of all resources in such a way that economics, social and aesthetic needscan be fulfilled while maintaining cultural integrity, essential ecological processes, biological diversityand life support system‟‟.Tourism is one of the biggest and fastest-growing economic sectors in the global economy and alsoworld‟s largest growing industry and has significant environmental, cultural, social, and economiceffects, both positive and negative. The main objectives of our study are formation of tourist circuits,promotion of eco-tourism, village tourism and find out the problems and suggest a suitable plan forsustainable tourism development in Uttarakhand and promote and propagation of local custom, cultureand traditional foods, dishes, folklore, handicrafts, architecture heritage etc, which have high valued atlocal communities but yet to set proper exploration recommendation to the world. Sustainable tourismcan be taken in four different interpretations that include socio-economic sustainability of tourism, theecologically sustainable tourism, sustainable tourism development with both focus of environment aswell as long term practicability of the industry and finally tourism as a part of a strategy for sustainabledevelopment. Therefore, the purpose of the present treaties is to adopt integrated approach andestablishment of new plans for the sustainable development of village eco-tourism in Kedar Valley withpilgrimage tourism in Uttarakhand.